A response to the paper by Arieh Y Shalev “Surviving the hardships of war. Brief advice on survival for civilians in the circumstances of war stress” - Chaban, Oleh (Psychosomatic Medicine and General Practice, 2022)
Professor Chaban’s response to Dr. Arye Shalev’s report "Surviving the hardships of war. Brief advice on survival for civilians in the circumstances of war stress"